EFEITO ANTITUMORAL DA MIRICETINA ASSOCIADO AOS MECANISMOS DE ADESÃO CELULAR EM LINHAGEM METASTÁTICA DE CÂNCER DE MAMA - SOUSA, Hiran Reis (2022)
Cancer is a pleiotropic disease caused by uncontrolled cell proliferation and is the second leading cause of death, after cardiovascular disease, worldwide. Recent surveys point to an acceleration in the number of cases that already cause death in one in eight men and in eleven women worldwide, of which lung and breast cancer are predominant. Cancer is a multifactorial disorder, presenting several conventional therapies for its treatment, which have enormous side effects due to their lack of specificity, being able to attack healthy cells. In the last two decades, phytochemicals have been studied as an alternative form of treatment and an adjunct to conventional anticancer therapy. Of the various polyphenol molecules that exhibited potent anticancer properties, myricetin was one of the substances that most stood out in recent years, as it has several pharmacological properties that also include antioxidant, anti-inflammatory, anticancer and epigenetic modulation activities. Therefore, our group set out to investigate the antitumor effect of myricetin through the mechanism of PDI inhibition by inducing oxidative stress in a tumor microenvironment model, using in vitro cytotoxicity assessment techniques and 3D cell culture techniques that mimic closer to in vivo, quantification of H2O2 and NO and co- culture with platelets. Our results show that myricetin promoted a cytotoxic effect in normal breast tissue cells, in a discrete way, and in breast cancer cells in a more accentuated and dose-dependent way, mainly in the lineage with greater invasive and metastatic power. It was also evident in our results that myricetin reduces the formation of spheroids and their stabilization, this effect being more expressive in MDA-MB-231 triple negative breast cancer cells, which are metastatic. There was an increase in the production of H2O2 and NO, in a dose-dependent manner and more evident in cells with more metastatic power and their levels consistent with levels of cell death signaling. There was a dose- dependent and more significant reduction in the interaction of tumor cells with platelets in the MDA-MB-231 lineage. Although there are many studies showings its cytotoxic effect on tumor cells, studies are unanimous in stating that there is much to be researched on the antineoplastic effect of myricetin, as its effect is proven to be broad on several molecular targets that involve the progression of different types of cancer, confirmed by different studies. Therefore, our next investigative steps will be to evaluate the oxidative stress of the tested cells and how myricetin interferes in cell interactions crucial for the formation and stabilization of spheroids, as well as in the formation of the physical shield of platelets with circulating tumor cells.